2018
DOI: 10.1038/s41375-018-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

CAR T-cells targeting FLT3 have potent activity against FLT3−ITD+ AML and act synergistically with the FLT3-inhibitor crenolanib

Abstract: FMS-like tyrosine kinase 3 (FLT3) is a transmembrane protein expressed on normal hematopoietic stem and progenitor cells (HSC) and retained on malignant blasts in acute myeloid leukemia (AML). We engineered CD8 and CD4 T-cells expressing a FLT3-specific chimeric antigen receptor (CAR) and demonstrate they confer potent reactivity against AML cell lines and primary AML blasts that express either wild-type FLT3 or FLT3 with internal tandem duplication (FLT3-ITD). We also show that treatment with the FLT3-inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
144
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 50 publications
6
144
2
1
Order By: Relevance
“…In line with our results, Lindl et al () reported that midostaurin inhibits CD123‐CD3 bsAb‐mediated cytotoxicity by inhibition of T‐cell proliferation in a dose‐dependent manner (IC 50 : 1 μmol/l). Jetani et al () described additive effects of a FLT3‐directed CAR T‐cell therapy at a low dose of 50 nmol/l midostaurin, which might explain some of the observed differences compared to our results. The immunosuppressive capacity of other TKIs, e.g.…”
contrasting
confidence: 89%
See 1 more Smart Citation
“…In line with our results, Lindl et al () reported that midostaurin inhibits CD123‐CD3 bsAb‐mediated cytotoxicity by inhibition of T‐cell proliferation in a dose‐dependent manner (IC 50 : 1 μmol/l). Jetani et al () described additive effects of a FLT3‐directed CAR T‐cell therapy at a low dose of 50 nmol/l midostaurin, which might explain some of the observed differences compared to our results. The immunosuppressive capacity of other TKIs, e.g.…”
contrasting
confidence: 89%
“…The number of autologous T cells increased upon CD33‐CD3 bsAb therapy alone, but the presence of midostaurin, completely abolished the proliferation of autologous T cells (Fig A). Recently, two independent research groups were able to show synergistic effects by combining FLT3‐selective TKIs with different T‐cell based immunotherapies (Jetani et al , ; Reiter et al , ). In these studies, low doses of either quizartinib (50 nmol/l) or crenolanolib (10 nmol/l) were applied.…”
mentioning
confidence: 99%
“…Likewise, two prior studies with T cells carrying CARs based on FLT3‐specific scFv antibody or FLT3 ligand reported normal human hematopoiesis in NSG mice transplanted with HSCs after treatment with the FLT3‐specific CAR T cells, and undisturbed colony formation of cord blood derived HSCs in the presence of CAR T cells, respectively . In contrast, in another recent report, a marked reduction in colony formation and HSC viability was observed upon exposure of HSCs to FLT3‐targeted CAR T cells . Here we did not observe CAR‐mediated killing of mobilized human CD34‐positive HSCs by NK‐92/4G8.28.z cells at the tested E/T ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups are also testing small molecules with the aim of improving CAR T cells efficacy. Jetani and colleagues recently reported that the FLT3 inhibitor crenolanib had a synergist activity with FLT3-directed CAR T cells in a FLT3-ITD AML model, at least in part by increasing FLT3 surface expression (79), and similar results were also presented for midostaurin (80). Besides, it was recently reported that PI3K inhibition can enhance CD33-directed CAR T cells durability, thus improving antitumor activity (81).…”
Section: Car T Cells For Myeloid Diseasesmentioning
confidence: 82%